Functionalized Magnetic Nanoparticles for the Detection and Quantitative Analysis of Cell Surface Antigen. (31st December 2013) - Shahbazi-Gahrouei, Daryoush; Abdolahi, Mohammad; Zarkesh-Esfahani, Sayyed Hamid; Laurent, Sophie; Sermeus, Corine; Gruettner, Cordula
Abstract : Cell surface antigens as biomarkers offer tremendous potential for early diagnosis, prognosis, and therapeutic response in a variety of diseases such as cancers. In this research, a simple, rapid, accurate, inexpensive, and easily available in vitro assay based on magnetic nanoparticles and magnetic cell separation principle was applied to identify and quantitatively analyze the cell surface antigen expression in the case of prostate cancer cells. Comparing the capability of the assay with flow cytometry as a gold standard method showed similar results. The results showed that the antigen-specific magnetic cell separation with antibody-coated magnetic nanoparticles has high potential for quantitative cell surface antigen detection and analysis.